2020
DOI: 10.1038/s41375-020-01043-x
|View full text |Cite
|
Sign up to set email alerts
|

IDH1/2 mutations in acute myeloid leukemia patients and risk of coronary artery disease and cardiac dysfunction—a retrospective propensity score analysis

Abstract: Clonal hematopoiesis of indeterminate potential (CHIP) is linked to leukemia gene mutations and associates with an increased risk for coronary artery disease and poor prognosis in ischemic cardiomyopathy. Two recurrently mutated genes in CHIP and adult acute myeloid leukemia (AML) encode for isocitrate dehydrogenases 1 and 2 (IDH1 and IDH2). Global expression of mutant IDH2 in transgenic mice-induced dilated cardiomyopathy and muscular dystrophy. In this retrospective observational study, we investigated wheth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 70 publications
(125 reference statements)
0
25
1
Order By: Relevance
“…3f). Intriguingly, contradicting previous studies involving other cohorts 40,41,43,44 , we observed the same for IDH1 mutations. This discrepancy might thus be attributed to specific characteristics of the WES AML cohort.…”
Section: Resultscontrasting
confidence: 99%
“…3f). Intriguingly, contradicting previous studies involving other cohorts 40,41,43,44 , we observed the same for IDH1 mutations. This discrepancy might thus be attributed to specific characteristics of the WES AML cohort.…”
Section: Resultscontrasting
confidence: 99%
“…IDH2 mutations were identified based on consequent genomic studies of IDH1 in AML [ 46 ]. Mutations in IDH proteins are found in 15–20% of AML cases [ 47 ]. Mutations in these genes are less common in MDS patients occurring in 3–5% of cases and 1–4% of MPN cases [ 48 ].…”
Section: Alterations In Dna Hydroxymethylationmentioning
confidence: 99%
“… 1 , 5 A single-center retrospective study reported on IDH -mutated AML to exhibit specific cardiac toxicity through 2-HG–dependent effects on cardiomyocytes when exposed to intensive chemotherapy, highlighting a possibly increased risk of treatment-related morbidity and mortality. 13 Overall, given the inconsistencies between studies, larger patient series will be needed to conclusively address the prognostic impact of IDH1/2 mutations.…”
Section: Idh -Mutated Aml and Response To Conventional Therapymentioning
confidence: 99%